2020
DOI: 10.1111/jam.14875
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic polyketides with siderophore mode of action from marine heterotrophic Shewanella algae : Prospective anti‐infective leads attenuate drug‐resistant pathogens

Abstract: Aims Biotechnological and chemical characterization of previously undescribed homologous siderophore‐type macrocyclic polyketides from heterotrophic Shewanella algae Microbial Type Culture Collection (MTCC) 12715 affiliated with Rhodophycean macroalga Hypnea valentiae of marine origin, with significant anti‐infective potential against drug‐resistant pathogens. Methods and Results The heterotrophic bacterial strain in symbiotic association with intertidal macroalga H. valentiae was isolated to homogeneity in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…68 As with previous reviews in this series, a number of new bacterial MNPs were claimed during 2021, but the structures presented were not fully consistent with the spectroscopic evidence provided. 7,30,31 The rst total syntheses of 22 marine bacterial compounds was reported in the literature during 2021, caprolactin C 6, 5 akazaoxime 4 and A-76356 45, 16 MA026 67, 25 xiamycins D and E, 69 bacicyclin, 70 (+)-pseudonocardide A and (+)-pseudonocardide C, 71 nocardiotide A, 72 three 2-(p-hydroxybenzyl)prodigiosin-based MNPs, along with isoheptylprodigiosin, and tambjamine MYP1, 73 (+)-spiroindimicin A, 74 nesteretal A, 75 (+)-03219A, 76 enterocin, 77 nahuoic acid A, 78 piscibactin, 79 and aldgamycin N. 80 Over 80 reviews featuring some aspect of marine bacterial chemistry or biology were published during 2021. This is the highest number of reviews ever and no doubt reects the impact that COVID-19 has had on labs around the world.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…68 As with previous reviews in this series, a number of new bacterial MNPs were claimed during 2021, but the structures presented were not fully consistent with the spectroscopic evidence provided. 7,30,31 The rst total syntheses of 22 marine bacterial compounds was reported in the literature during 2021, caprolactin C 6, 5 akazaoxime 4 and A-76356 45, 16 MA026 67, 25 xiamycins D and E, 69 bacicyclin, 70 (+)-pseudonocardide A and (+)-pseudonocardide C, 71 nocardiotide A, 72 three 2-(p-hydroxybenzyl)prodigiosin-based MNPs, along with isoheptylprodigiosin, and tambjamine MYP1, 73 (+)-spiroindimicin A, 74 nesteretal A, 75 (+)-03219A, 76 enterocin, 77 nahuoic acid A, 78 piscibactin, 79 and aldgamycin N. 80 Over 80 reviews featuring some aspect of marine bacterial chemistry or biology were published during 2021. This is the highest number of reviews ever and no doubt reects the impact that COVID-19 has had on labs around the world.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
“…Chemical mining of Shewanella algae extracts identified four new macrocyclic polyketides 93–96 . 30,31 Whilst a total of 20 genera of marine-derived bacteria contributed to new chemistry reported in 2021, the genus Streptomyces continues to be the predominant source with 120 metabolites. The new MNPs from this prolific genus included two antibacterial spirotetronate derivatives, lobophorins L 97 and M 98 , 32 two trioxacarcins congeners 99 , 100 , 33 cytotoxic isoquinolinequinones named mansouramycins E–G 101–103 , 34 a rare benzo[ f ]isoindole-dione alkaloid 104 , 35 linear azole-containing peptides spongiicolazolicins A 105 and B 106 , 36 antimycin-type depsipeptides, zhaoshumycins A 107 and B 108 , 37 along with four antimicrobial chlorinated carbazole alkaloids named chlocarbazomycins A–D 109–112 .…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…Two new siderophore-type hydroxyfuranyl-benzoate spanned 12-membered macrocyclic polyketides 23 and 24 were isolated from Shewanella algae MTCC 12715, and displayed broad antibacterial activities against multiple clinical pathogens including MRSA (inhibition zones of 23 mm and 29 mm, respectively) and P. aeruginosa (inhibition zones of 21 mm and 24 mm, respectively) [ 41 ]. In order to verify their in vitro anti-microbial activities against MRSA, in silicon docking studies for 23 and 24 with penicillin-binding protein 2a (PBP2a), a transpeptidase that catalyzes cell-wall crosslinking to counter the effect of β-lactam antibiotics.…”
Section: Emerging Mnps As Promising Antibiotics For Inhibiting ...mentioning
confidence: 99%
“…Docking studies indicated that both compounds could occupy the allosteric site of PBP2a with predicted K i values of 17.51 nM and 3.57 nM, respectively. Besides, compound 24 has a higher drug-likeness score of 0.91 than that of 23 [ 41 ].…”
Section: Emerging Mnps As Promising Antibiotics For Inhibiting ...mentioning
confidence: 99%
“…The molecules were chemically characterized as 14-(14b,14c-dimethylbutyl)-12-methoxy-18-oxo-11,15-dioxacyclododecan-8-yl 1-((50-hydroxyfuran-10-yl)oxy)benzoate ( 1 ), and 14-(sec-butyl)-12-methoxy-12-methyl-18-oxo-11,15-dioxacyclododecan-8-yl1-((50-hydroxyfuran-10-yl)oxy)benzoate ( 2 ). Compounds 1 and 2 showed antimicrobial activity against P. aeruginosa with an inhibition halo of 21 and 24 mm diameter in DDA and MIC values of 1.5 and 3 µg/mL, respectively [ 135 ].…”
Section: Marine Natural Products Against P Aeruginosamentioning
confidence: 99%